STUDY OF GEOCHEMICAL CHARACTERIZATION OF ACID MINE DRAINAGE FORMATION AND RECOMMENDATIONS FOR OVERBURDEN DUMPING AT PT XYZ COAL MINE - Rafsanjani, Rafy
Mining activities can alter the landscape, which can lead to changes in environmental conditions, thereby allowing for changes in the physical and chemical properties of rocks. These changes can affect water quality, and if it shows a high level of acidity, then the water is classified as acid mine drainage or AMD. A geochemical characterization study of the rocks at the mining site is a crucial first step in predicting the potential formation of acid mine drainage. By understanding the potential formation of AMD, it is hoped that plans and strategies for preventing AMD can be identified. One of the methods is by using encapsulation in the area of overburden rock deposits. In this study, geochemical characterization of rock samples was conducted, which were collected through grab and core sampling during a field visit to PT XYZ. The geochemical characterization of the rock samples was conducted using static tests, and the results will be used to create a geochemical model divided into two areas: the northern pit area and the southern pit area. The results of the geochemical characterization conducted through static testing revealed that there are 11 rock samples that are acid-generating or PAF (potentially acid forming) and 9 rock samples that are non-acid generating or NAF (non-acid forming). The results of the geochemical characterization of the rocks were used to create geochemical models for each pit area. In the northern pit area, based on the geochemical characterization from 12 samples, it was found that 63% of the rocks are PAF and 37% are NAF. In the southern pit area, based on the geochemical characterization from 8 samples, 80% of the rocks are PAF and 20% are NAF. The results of the geochemical model and the annual overburden production plan are used to generate designs and strategies for the planning of PAF and NAF rock storage using encapsulation methods.